PARENTAL GENOME DIFFERENTIATION BY GENOMIC IN SITU HYBRIDIZATION (GISH) IN INTERGENERIC HYBRID OF SACCHARUM X ZEA - Sobhakumari, VP (Journal of Sugarcane Research, 2020)
Tissue culture plants were developed from a rare non flowering hybrid of Saccharum officinarum (Vellai,2n=80) x Zea mays (Golden Beauty 2n= 20+2B). Flowering was induced and the cytogenetic studies revealed that the number of chromosomes varies in root tip cells of the tissue cultured plants form 2n=52-56. The increase in chromosome number was due to the accumulation of B chromosomes. Genomic in situ hybridization (GISH) with Zea probe could reveal only repetitive sequences in the hybrid genome but not the whole chromosomes of Zea and this may be due to the rearrangements and loss of genome sequences especially in the maize which is rich in transposons and retrotransposons in its genome. GISH with Saccharum probe identifies 40 chromosomes of S. officinarum and 10+2B chromosomes of Zea mays in the hybrid. In situ hybridization with Saccharum probe was also revealed the homeology between the two genomes.